Estimating sea-ice volume flux out of the Laptev Sea using multiple satellite observations. Issue 1 (1st January 2016) - Bi, Haibo; Huang, Haijun; Fu, Min; Fu, Tengfei; Zhou, Xuan; Xu, Xiuli
Abstract : Sea-ice outflow from the Laptev Sea is of considerable importance in maintaining the Arctic Ocean sea-ice budget. In this study, a method exclusively using multiple satellite observations is used to calculate sea-ice volume flux across the eastern boundary (EB) and northern boundary (NB) of the Laptev Sea during the October–November and February–March or March–April periods (corresponding to the ICESat autumn and winter campaigns) between 2003 and 2008. Seasonally, the mean total ice volume flux (i.e., NB+EB) over the investigated autumn period (1.96 km 3 /day) is less than that over the winter period (2.57 km 3 /day). On the other hand, the large standard deviations of the total volume flux, 3.45 and 0.91 km 3 /day for the autumn and winter campaigns, indicate significant interannual fluctuations in the calculated quantities. A statistically significant ( P >0.99) positive correlation, R =0.88 (or 0.81), is obtained between volume flux across the EB (or NB) and mean ice-drift speed over the boundary for the considered 11 ICESat campaigns. In addition, statistics show that a large fraction of the variability in volume flux across the NB over the 11 investigated campaigns, roughly 40%, is likely explained by ice thickness variability. On average, flux through the Laptev Sea amounts to approximately one-third of that across Fram Strait during the autumn and winter campaigns. These large contributions of sea ice from the Laptev Sea demonstrate its importance as an ice source, affecting the entire sea-ice mass balance in the Arctic Ocean.